TLR4-NLRP3-GSDMD-Mediated Pyroptosis Plays an Important Role in Aggravated Liver Injury of CD38-/- Sepsis Mice - Huiqing Zhang; Yuna Du; Yujie Guo; Zeyu Wang; Hua Li; Zhe Lv; Lifeng Zeng; Yiguo Chen; Zhengyu Xie; Rong Li (Journal of Immunology Research)
Clinically, severe bacterial infection can cause septicemia and multiple organ dysfunction syndrome, especially liver injury. CD38 is closely related to many inflammatory pathways, but its role in liver injury caused by bacterial infection remains unclear. The purpose of this study is to discuss the specific role of CD38 in bacterial liver injury. Eight-week-old male C57BL/6 mice (WT, CD38-/- and CD38-/-TLR4mut) were used and stimulated with Escherichia coli (ATCC25922) or PBS, intraperitoneally. After 3 hours of bacterial stimulation, serum was collected to detect ALT and AST concentration, and liver tissue was harvested for hematoxylin and eosin staining and bacterial culture. The mRNA expressions of TLR4, NLRP3, IL-1β, IL-18, and GSDMD were quantitatively determined by RT-qPCR. The expressions of TLR4, MyD88, TRIF, NF-κB p65, NLRP3, GSDMD, and cytokines were detected by Western blot. The expression and localization of ERK1/2 were detected by immunohistochemistry and Western blot. The results showed that bacterial stimulation could upregulate the expression of inflammatory cytokines, leading to hepatic dysfunction. Moreover, bacterial stimulation of CD38-deficient mice can aggravate the inflammatory response, the expressions of TLR4, NF-κB, and ERK1/2 were significantly increased, and the biomarkers related to pyroptosis also manifested more obvious pyroptosis. However, TLR4 mutation significantly alleviated inflammation and pyroptosis in the liver caused by bacteria, on the basis of CD38 deficiency. Overall, CD38 knockout exacerbates bacteria-induced liver damage through TLR4-NLRP3-GSDMD-mediated pyroptosis.